2019
DOI: 10.2478/topling-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

But, you see, the problem is …Perception verbs in courtroom talk: Focus onyou see

Abstract: This article seeks to contribute to the body of research on the use of perception verbs in interaction and, more specifically, to enhance the understanding of how participants in courtroom proceedings exploit you see to manage the discourse as it unfolds and to negotiate stance. Against the background of earlier work on vision words in interaction, the study looks at parenthetical and non-parenthetical you see to reveal both perceptual and cognitive uses, and to identify their local pragmatic effect. As the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This measure revealed that respect, respectful and respectfully occurred 16, 128 and 2,048 times more frequently in our corpus than in the Spoken BNC2014. 5 In focusing on one word or lemma as a means of analysing pragmatic patterns in a large corpus of courtroom discourse, this paper follows an emerging trend in the field, with well (Tkacukova 2015), now (Claridge 2018), you see (Szczyrbak 2019) and but (Lutzky 2019) having all recently been used for this purpose.…”
Section: Whilst Of Lord Pannick Qc He Saidmentioning
confidence: 99%
“…This measure revealed that respect, respectful and respectfully occurred 16, 128 and 2,048 times more frequently in our corpus than in the Spoken BNC2014. 5 In focusing on one word or lemma as a means of analysing pragmatic patterns in a large corpus of courtroom discourse, this paper follows an emerging trend in the field, with well (Tkacukova 2015), now (Claridge 2018), you see (Szczyrbak 2019) and but (Lutzky 2019) having all recently been used for this purpose.…”
Section: Whilst Of Lord Pannick Qc He Saidmentioning
confidence: 99%